Entrevista semiestructurada para la aplicación de autopsia psicológica en el Ecuador: componentes sociodemográfico, clínico y personalidad y características psicosociales. - Jaramillo, Juan F. (2020)
Death is an event that we all view with suspicion. when we have it close, disturbs us and, without a doubt, arises in us, almost involuntarily, an interest particular to know the causes of this event. It is precisely this concern been present in humanity since its inception and is currently the focus of study of some forensic sciences. In the field of criminology, when faced with doubtful deaths, competent professionals in the field of criminal investigation are unable to deliver an unequivocal verdict on the factors surrounding the death of a person, because they do not have abundant, evident and conclusive information that let them do it. Thus, the technical figure Psychological Autopsy (AP) arises as post-mortem application tool, aimed at obtaining useful information and for criminal investigation in this type of situation (Núñez de Arch, 2005).